A randomized phase 2 trial of nivolumab, gemcitabine, and cisplatin or nivolumab and ipilimumab in previously untreated advanced biliary cancer: BilT‐01. Issue 19 (27th July 2022) - Sahai, Vaibhav; Griffith, Kent A.; Beg, Muhammad S.; Shaib, Walid L.; Mahalingam, Devalingam; Zhen, David B.; Deming, Dustin A.; Zalupski, Mark M.
Abstract : Background: Gemcitabine and cisplatin has limited benefit as treatment for advanced biliary tract cancer (BTC). The addition of an anti‐programmed death receptor (PD‐1)/PD‐ligand (L1) antibody to either systemic chemotherapy or anti‐cytotoxic T‐lymphocyte‐associated protein 4 (CTLA4) antibody has shown benefit in multiple solid tumors. Methods: In this phase 2 trial, patients 18 years or older with advanced BTC without prior systemic therapy and Eastern Cooperative Oncology Group Performance Status 0–1 were randomized across six academic centers. Patients in Arm A received nivolumab (360 mg) on day 1 along with gemcitabine and cisplatin on days 1 and 8 every 3 weeks for 6 months followed by nivolumab (240 mg) every 2 weeks. Patients in Arm B received nivolumab (240 mg) every 2 weeks and ipilimumab (1 mg/kg) every 6 weeks. Results: Of 75 randomized patients, 68 received therapy (Arm A = 35, Arm B = 33); 51.5% women with a median age of 62.5 years. The observed primary outcome of 6‐month progression‐free survival (PFS) rates in the evaluable population was 59.4% in Arm A and 21.2% in Arm B. The median PFS and overall survival (OS) in Arm A were 6.6 and 10.6 months, and in Arm B 3.9 and 8.2 months, respectively, in patients who received any treatment. The most common treatment‐related grade 3 or higher hematologic adverse event was neutropenia in 34.3% (Arm A) and nonhematologic adverse events were fatigue (8.6% Arm A) and elevated transaminases (9.1% Arm B). Conclusions: The addition of nivolumab to chemotherapy or ipilimumab did not improve 6‐month PFS. Although median OS was less than 12 months in both arms, the high OS rate at 2 years in Arm A suggests benefit in a small cohort of patients. Abstract : Immune checkpoint inhibition alone or in combination with chemotherapy as first‐line therapy does not appear to improve efficacy when compared to chemotherapy alone for patients with advanced biliary cancer in the United States. However, at least one third of the patients were alive at 2 years in the chemoimmunotherapy arm, and additional studies are ongoing to investigate this result, and importantly, evaluate biomarkers predictive for benefit from this treatment regimen.